PENERAPAN SANKSI PIDANA TERHADAP PELAKU PENYELUNDUPAN ORANG DI INDONESIA - Sitorus, Samson Hasonangan; Afrita, Indra; Winstar, Yelia Nathassa (LPPM STIH Awang Long, 2024)
The purpose of this research is to analyze the application of criminal sanctions against human trafficking offenders in Indonesia, and to examine the legal consequences of applying these sanctions. The method used is sociological legal research. Based on the research findings, the application of criminal sanctions against human trafficking offenders in Indonesia demonstrates the state's commitment to protecting victims and combating human trafficking crimes. Existing laws provide a strong legal basis for firmly addressing offenders, yet in the application of judicial decisions based on the above, judges and prosecutors impose lower penalties, namely Articles 81, 82, 83, and 86 of Indonesian Law No. 18 of 2017 concerning the Protection of Indonesian Migrant Workers and Articles 2, 3, 4, and 10 of Indonesian Law No. 21 of 2007 concerning the Eradication of Human Trafficking. However, more severe penalties aimed at deterrence should ideally be stipulated under Article 120 of Law No. 6 of 2011 concerning Immigration. Human smuggling crimes are classified as serious offenses threatening security and human rights. The legal consequences of applying criminal sanctions against human trafficking offenders in Indonesia include severe punishments such as imprisonment and fines commensurate with the severity of the crimes committed. Moreover, offenders may face additional sanctions such as asset confiscation obtained from illegal activities. The imposed penalties aim to deter both the perpetrators and the general public, serving as a preventive measure against the recurrence of similar crimes and as a warning to those involved in illegal activities. Handling human trafficking crimes also involves aspects of victim protection. Thus, the application of criminal sanctions against human trafficking offenders in Indonesia not only impacts the individual perpetrators but also reflects the state's efforts to strengthen legal protection of human rights and national security.